Development of social tourism in Ukraine - Vorvul, A. S.; Pererva, P. G. (My University, 2023)
It is substantiated that the concept of "social management" characterizes the process of influencing society or its separate links with the aim of ensuring their normal functioning, improvement and development. There are other characteristics according to which social management is limited to the sphere of activity of certain bodies or economic, technical, legal and other frameworks.
Розвиток соціального туризму в Україні
Keywords: social tourism; implementation; advertising; definition; business; efficiency